Efficacy and safety of tripterygium glycosides in the treatment of hyperthyroidism: A systemic review and meta-analysis. Issue 38 (18th September 2020) - Xie, Chunyan; He, Chaozhu; Gao, Jun; Jia, Shulei
Abstract: Background: Hyperthyroidism is a condition in which the thyroid gland is overreactive and produces excess amounts of thyroid hormone. Tripterygium glycosides, traditional Chinese medicine has been widely used in the treatment of rheumatoid arthritis, nephrotic syndrome, hyperthyroidism and other diseases due to its anti-inflammatory and immunosuppressive effects. Evidence-based research is becoming popular especially with the application of Chinese traditional medicine. This paper systematically reviews and evaluates existing clinical data on the efficacy and safety of Tripterygium glycosides in the treatment of hyperthyroidism. Materials and methods: PubMed, Cochrane library and EMBase, Chinese biomedical literature database (CBM), Chinese journal full-text database (CNKI), Wan fang digital periodical full-text database and China Science and Technology Journal Database (VIP) were searched based on the defined inclusion and exclusion criteria. Data extraction, research quality assessment and meta-analysis were conducted with RevMan5.3 software. Trial sequential analysis (TSA) was used to evaluate information size and treatment benefits. Results: Seventeen randomized controlled clinical trials with 1536 participants were included in the systematic review. In the meta-analysis, there were two subgroups: Tripterygium glycosides combined with thiamazole and prednisone group; Tripterygium glycosides combined with thiamazole group. The study results revealed that the degree of exophthalmos, FT3, FT4, BGP, and AKP decreased while TSH, SOD, GSH-PX increased after the addition of Tripterygium glycosides. This study results suggested that Tripterygium glycosides combined with western medicine are an effective therapy for hyperthyroidism. Conclusion: This study indicates that Tripterygium glycosides enhances the effect of thiamazole and prednisone in the treatment of hyperthyroidism and without increasing the risk of adverse events.